Hubungan Dukungan Suami Dengan Perilaku Pola Konsumsi Nutrisi Pada Ibu Hamil - Putri, Silvia Adila; Indriyani, Diyan; Kholifah, Siti (Indonesian Journal Publisher, 2025)
Background: Pregnant women are a group at risk when faced with nutrition, therefore husband's support is needed. Objective: To analyze the relationship between husband's support and nutritional consumption behavior in preventing chronic energy deficiency (CED) in pregnant women in the Silo II Community Health Center work area. Method: Correlational design using a cross-sectional approach. The study population was 83 pregnant women, calculated using the Slovin formula with 69 respondents. The sampling technique used was cluster random sampling. Data were collected through questionnaires. Data analysis was carried out using the Spearman Rho method with α ≤ 0.05. Results: The results of the study showed that most pregnant women received optimal support from their husbands, with a percentage of 75.4% and the majority of pregnant women's nutritional consumption behavior was compliant, with a percentage of 82.6%. The results of the analysis showed a significant and strong relationship. Conclusion: A strong relationship exists between husband's support and nutritional consumption behavior in preventing chronic energy deficiency (CED) in pregnant women in the Silo II Community Health Center work area. Husbands can increase information support, attention, and involvement in fulfilling nutritional needs during pregnancy by providing information obtained from social media, magazines, books, and pamphlets.